Studies in the enzymology of glutathione metabolism in human erythrocytes - Jackson, R. C. (1969)
Spectrophotometric assay methods are described for glutathione synthetase, γ-glutamylcysteine synthetase and γ-glutamyl transpeptidase of erythrocytes. The contents of these enzymes in normal human erythrocytes are reported. Erythrocyte glutathione synthetase is inhibited by ADP; this inhibition is competitive with respect to ATP. γ-Glutamylcysteine synthetase is subject to feedback inhibition by GSH, and is also inhibited by NADH, and to a lesser extent by NAD(+) and NADPH. This enzyme is irreversibly inactivated by cysteamine.